Efficient gene therapy-based method for the delivery of therapeutics to primate cortex - Kells, Adrian P. (National Academy of Sciences, 2009)
Transduction of the primate cortex with adeno-associated virus (AAV)-based gene therapy vectors has been challenging, because of the large size of the cortex. We report that a single infusion of AAV2 vector into thalamus results in widespread expression of transgene in the cortex through transduction of widely dispersed thalamocortical projections. This finding has important implications for the treatment of certain genetic and neurodegenerative diseases.